Kinematic analysis of three link spatial mechanisms containing sphere plane and sphere-groove pairs - Hernandez, Manuel V.
Kinematic pairs in a spatial mechanism are viewed either as allowing relative screw motion between links or as constraining the motion of the two chains of the mechanism connected to the two elements of the pair.